PENGARUH MODEL PEMBELAJARAN CONNECTED MATHEMATICS PROJECT (CMP) TERHADAP KEMAMPUAN REPRESENTASI MATEMATIS SISWA SMP NEGERI 2 MUARA SUGIHAN - Wahyuningsih Wahyuningsih; Jumroh Jumroh; Yunika Lestaria N (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2017)
This study aimed at determining whether there is influence of learning model Connected Mathematics Project (CMP) to the ability of mathematical representation of students of SMP Negeri 2 Muara Sugihan. The ability of this mathematical representation includes 3 indicators of mathematical representation 1) in the form of diagrams, graphs, tables and drawings, 2) Mathematical equations or expressions and, 3) written words or texts. The method used in this research was posttest only control design model. The population in this study were the entire class VIII in SMP Negeri 2 Muara Sugihan. The sample were taken in this research for experimental class was class VIII 2 was given approach of Connected Mathematics Project (CMP) and control class VIII 3 was given expository learning. Technique of collecting data in this research was written test. Data analysis technique used was T-test. This test refers to an indicator of the ability of a mathematical representation. Based on the calculation results obtained tcalcule = 5.836 and ttable = 1.998. It can be concluded that there is a significant influence of Connected Mathematics Project (CMP) model of mathematical representation of students of SMP Negeri 2 Muara Sugihan.